Efficacy and safety of capsaicin 8% patches: The experience of a rheumatology department - Sylvain Mathieu; Marion Couderc; Marine Beauger; Sandrine Malochet-Guinamand; Marie-Eva Pickering; Martin Soubrier; Anne Tournadre (SAGE Open Medicine)
Background: Capsaicin 8% patches are recommended for the treatment of localized neuropathic pain, which is a frequent reason for rheumatology consultations. Objectives: This study aimed to evaluate the efficacy and safety of capsaicin 8% used in our Rheumatology Department. Design: Single-center retrospective study. Methods: Patients treated by capsaicin 8% between October 03, 2019 and December 31, 2023 were included. Their age, sex, pain duration, DN4 score, pain intensity, and the cause of the neuropathic pain were collected. Patch safety was assessed on the day of application and after 15 days. The patient was asked about improvement, pain intensity, and the occurrence of burning sensations. Results: One hundred twelve patients (mean age 62, 70% female) were included. The causes of neuropathic pain were especially scar ( n = 31), digital osteoarthritis ( n = 26), or radiculalgia ( n = 22). Sixty patients reported improvement (54%) at day 15, with a mean percentage of improvement of 59%. Mean pain intensity decreased from 6.4 ± 1.9 to 4.5 ± 2.7 ( p < 0.001). This improvement in pain was significant regardless of etiology. There was no difference in age, sex, and pain duration between improved and unimproved patients. Fifty-eight patients (58/106: 54.7%) experienced burning sensations after patching, mainly of moderate to high intensity (32/52: 61.5%), with an average duration of 2 days. Of the eight unimproved after the first patch, six reported a 50% improvement after the second patch. Conclusion: Capsaicin 8% appeared to be an effective treatment in localized neuropathic pain, whatever the cause. It seemed beneficial to repeat the application after the 1st one had failed. Burning sensations after placement were fairly frequent, usually moderate to high, but lasting only a short time.